Using Optical Coherence Tomography to Evaluate Skin Sun Damage and Precancer - Korde, Vrushali R. (2007)
BACKGROUND AND OBJECTIVES: Optical coherence tomography (OCT) is a depth resolved imaging modality that may aid in identifying sun damaged skin and the precancerous condition actinic keratosis (AK). STUDY DESIGN/MATERIALS AND METHODS: OCT images were acquired of 112 patients at 2 sun protected and 2 sun exposed sites, with a subsequent biopsy. Each site received a dermatological evaluation, a histological diagnosis, and a solar elastosis (SE) score. OCT images were examined visually and statistically analyzed. RESULTS: Characteristic OCT image features were identified of sun protected, undiseased, sun damaged, and AK skin. A statistically significant difference (P < 0.0001) between the average attenuation values of skin with minimal and severe solar elastosis was observed. Significant differences (P < 0.0001) were also found between undiseased skin and AK using a gradient analysis. Using image features, AK could be distinguished from undiseased skin with 86% sensitivity and 83% specificity. CONCLUSION: OCT has the potential to guide biopsies and provide non-invasive measures of skin sun damage and disease state, possibly increasing efficiency of chemopreventive agent trials.